2022
DOI: 10.1093/ajcn/nqac223
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of iron from edible house crickets: a randomized crossover stable-isotope study in humans

Abstract: Background Edible insects are a novel source of animal protein. Moreover, edible insects contain iron concentrations similar to meat, potentially making them a valuable iron source for human consumers. Yet, it is unknown to what extent iron from insects is absorbed in humans. Objectives In this exploratory study, we assessed fractional iron absorption from house crickets (Acheta domesticus) consumed with refined (low-phytate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A comparable isotopic study was conducted to assess fractional iron absorption of maize porridge enriched with whole yellow mealworm powder or its dechitinized protein fraction in 21 females [18 ▪ ]. Contrary to findings of Mwangi et al [17 ▪ ], iron was moderately well absorbed with no differences between whole mealworms or its dechitinized protein fraction. The discrepancy in outcomes between these studies may be attributed to differences in iron and chitin abundance between the insect species, as well as in the structural properties of chitin during metamorphic stages of the insects, or differences in the presence of other antinutrient components.…”
Section: Micronutrientsmentioning
confidence: 91%
See 2 more Smart Citations
“…A comparable isotopic study was conducted to assess fractional iron absorption of maize porridge enriched with whole yellow mealworm powder or its dechitinized protein fraction in 21 females [18 ▪ ]. Contrary to findings of Mwangi et al [17 ▪ ], iron was moderately well absorbed with no differences between whole mealworms or its dechitinized protein fraction. The discrepancy in outcomes between these studies may be attributed to differences in iron and chitin abundance between the insect species, as well as in the structural properties of chitin during metamorphic stages of the insects, or differences in the presence of other antinutrient components.…”
Section: Micronutrientsmentioning
confidence: 91%
“…Inclusion of the highest amount of cricket flour (7.5 g/100 g) led to higher levels of PUFA. A study by Ochieng et al [14 ] also found that adding grasshoppers to cookies increased the amounts of PUFAs. For nutritional value in children' diets, insects should be evaluated species by species for accurate determination of lipids.…”
Section: Fatmentioning
confidence: 92%
See 1 more Smart Citation
“…Iron occurs predominantly in nonhaem forms, bound to ferritin and transferrin and other transport and storage proteins (Mwangi et al, 2018). In a stable isotope absorption study undertaken in iron-depleted women, Mwangi et al (2022) found that iron absorption from intrinsically labelled house crickets (Acheta domesticus) added to maize porridge was low (~3%) which they suggested might be due to the presence of chitin and other inhibitors in the cricket biomass. A study of similar design examined iron absorption from mealworm larvae (Tenebrio molitor) and found it was similar to maize porridge (~5%); processing of the T. molitor biomass to reduce the chitin content did not increase iron bioavailability (Hilaj et al, 2022).…”
Section: Effect Of Meat On Non-haem Iron Absorptionmentioning
confidence: 99%
“…Furthermore, two recent RCT conducted in young females (18–45 years) reported conflicting results. While mealworm fortification [ 23 ] seems to provide a high non heme iron absorption, house rickets [ 24 ] showed a low iron absorption rate. No study to date has evaluated this specific topic in children.…”
Section: Main Textmentioning
confidence: 99%